Pathology Milestones - J. Stacey Klutts MD, PhD; Leana A. Guerin MD; Leslie A. Bruch MD; Dennis J. Firchau MD; C. Michael Knudson MD, PhD; Nancy S. Rosenthal MD; Megan I. Samuelson MD; Chris S. Jensen MD; Janet L. Delwiche BA; Matthew D. Krasowski MD, PhD (Elsevier, 2015)
All Accreditation Council for Graduate Medical Education accredited pathology residency training programs are now required to evaluate residents using the new Pathology Milestones assessment tool. Similar to implementation of the 6 Accreditation Council for Graduate Medical Education competencies a decade ago, there have been challenges in implementation of the new milestones for many residency programs. The pathology department at the University of Iowa has implemented a process that divides the labor of the task in rating residents while also maintaining consistency in the process. The process is described in detail, and some initial trends in milestone evaluation are described and discussed. Our experience indicates that thoughtful implementation of the Pathology Milestones can provide programs with valuable information that can inform curricular changes.